The Role of Continuous Improvement Strategy (Kaizen) in organizational innovation: An analytical research in the General Company of Electrical and Electronic Industries /The Ministry of Industry and Minerals - Khalil, Asra Abdu Al salam; Hamid, Suhair Adel (Journal of Economics and Administrative Sciences, 2021)
This paper aims at the fact that most organizations today suffer from a waste of time, effort, and cost, and they have difficulty in achieving the best performance situations and compete strongly. The researcher distributed 108 questionnaires as a statistical analyzable sample society where the sample intentionally consists of general managers, department head, and division head. The questionnaire was formulated according to the Likert scale. The use of personal interviews and observations are additional tools for data collection and a number of statistical methods is used for data analysis such as simple regression and correlation coefficient (Pearson). One of the most prominent conclusions is that the company has adequate and creative capabilities on the ground and for the production of Iraqi does not have competitive and creative capabilities and must work on the development of new methods in the administrative work within the company. The results also show the lack of conviction difficulties and turn them into opportunities that promote creative work, expand growth opportunities and create cadres that start creative work and experience the element of risk. Engaging employees in training courses can acquire or increase their skills